PEMANFAATAN BONGGOL PISANG UNTUK PEMBUATAN ASAM PHOSPAT - Nurma Wahyusi, Kindriari (Jurnal Teknik Kimia, 2008)
Banana a tropical and subtropical tree with good prospect found anywhere in Indonesia which easy to cultivateand rapidly. Concerning the chemical composition, the hump banana tree contain phosphorous large enoughe.Using special treatment and adding sulfuric acid alkali, the phosphorous content at the hump banana tree couldbe processed to produce phosphoric acid.The objective of research is to produce phosphoric acid from the hump banana tree waste as the syntheticfertilizer as follows : TSP, NPK etc. it also can be used as sugar cane substance to remove the impurities. Hopethe research will be worthwhile and value for hump banana tree waste.There are two process steps i.e. : The process which contain calcium and phosphorous to compound calciumphosphate. Then the phosphoric acid compound process. It also produces gypsum at the reaction. This research’sresult showed that 3 hours and sulfuric acid concentration of 60 % could reduce phosphorous convertionoptimum i.e. : 0,79 was obtained at ambon banana.Key words : hump banana tree, phosphoric acid.